Diversification of the Histone Acetyltransferase GCN5 through Alternative Splicing in Brachypodium distachyon - Martel, Alexandre; Brar, Hardev; Mayer, Boris F.; Charron, Jean-Benoit (Frontiers in Plant Science, 2017)
The epigenetic modulatory SAGA complex is involved in various developmental and stress responsive pathways in plants. Alternative transcripts of the SAGA complex’s enzymatic subunit GCN5 have been identified in Brachypodium distachyon. These splice variants differ based on the presence and integrity of their conserved domain sequences: the histone acetyltransferase domain, responsible for catalytic activity, and the bromodomain, involved in acetyl-lysine binding and genomic loci targeting. GCN5 is the wild-type transcript, while alternative splice sites result in the following transcriptional variants: L-GCN5, which is missing the bromodomain and S-GCN5, which lacks the bromodomain as well as certain motifs of the histone acetyltransferase domain. Absolute mRNA quantification revealed that, across eight B. distachyon accessions, GCN5 was the dominant transcript isoform, accounting for up to 90% of the entire transcript pool, followed by L-GCN5 and S-GCN5. A cycloheximide treatment further revealed that the S-GCN5 splice variant was degraded through the nonsense-mediated decay pathway. All alternative BdGCN5 transcripts displayed similar transcript profiles, being induced during early exposure to heat and displaying higher levels of accumulation in the crown, compared to aerial tissues. All predicted protein isoforms localize to the nucleus, which lends weight to their purported epigenetic functions. S-GCN5 was incapable of forming an in vivo protein interaction with ADA2, the transcriptional adaptor that links the histone acetyltransferase subunit to the SAGA complex, while both GCN5 and L-GCN5 interacted with ADA2, which suggests that a complete histone acetyltransferase domain is required for BdGCN5-BdADA2 interaction in vivo. Thus, there has been a diversification in BdGCN5 through alternative splicing that has resulted in differences in conserved domain composition, transcript fate and in vivo protein interaction partners. Furthermore, our results suggest that B. distachyon may harbor compositionally distinct SAGA-like complexes that differ based on their histone acetyltransferase subunit.